Penggunaan Media Komik Untuk Meningkatkan Keterampilan Membaca Siswa Kelas IV B SD Inpres 2 Tondo - Dela Anggraini; Kasmawati; Roberto Rolly Bulalong (JURNAL DIKDAS, 2026)
Skills of fourth-grade students at SD Inpres 2 Tondo through the use of comic learning media. The research employed a Classroom Action Research (CAR) design with two learning cycles integrating Problem Based Learning (PBL) and Discovery Learning models. The subjects were 19 fourth-grade students. Data were collected through motivation questionnaires and observation of teacher and student activities. The results showed significant improvement in students' reading skills, with average scores increasing from 68.7 (fair category) in cycle I to 83.2 (good category) in cycle II. Teacher and student activities also improved, reflecting more structured learning and higher student participation. Comic media proved effective in capturing students’ attention, motivating them to read, and creating a conducive learning atmosphere. The study recommends the use of comic media as an innovative alternative in Indonesian language learning at the elementary school level.